Time series analysis and scaling law characteristics of viral hepatitis from 2004 to 2023 in Zhejiang Province, China - Ming Xue; Chen Wu; Kui Liu; Qinbao Lu; Zheyuan Ding; Xinyi Wang; Tianyin Fu; Junfen Lin; Haocheng Wu (PLoS ONE, 2025)
Background Hepatitis significantly increases the global disease burden and has become a major public health issue worldwide. China is a high-risk area for viral hepatitis, which is also a serious public health problem. Methods The scaling relationship between various types of hepatitis and population size was explained by a scaling law. Fixed-effects and random-effects meta-analyses were used to calculate a combined index of β based on the single-scale index from 2004 to 2023. Furthermore, the X11 process was employed to identify the structural components of the time series of various types of hepatitis. Results In the past 20 years, the proportion of patients with viral hepatitis in Zhejiang Province has changed significantly, and hepatitis B remains the main type of hepatitis, accounting for approximately 70% of all hepatitis cases. The proportion of hepatitis C and E cases has been increasing, whereas the proportion of hepatitis A cases has been decreasing since 2004 and has remained at a low level (approximately 3%) since 2010. The combined scaling exponents of hepatitis A, hepatitis B, hepatitis C, hepatitis E and unclassified hepatitis based on the random effects model were 0.88 (95% confidence interval(CI): 0.78 to 0.98), 0.78 (95% CI: 0.70 to 0.86), 1.18 (95% CI: 1.11 to 1.26), 0.91 (95% CI: 0.86 to 0.97) and 0.89 (95% CI: 0.79 to 1.00), respectively. Conclusion In the past 20 years, the epidemic situation of hepatitis A, hepatitis B and unclassified hepatitis has shown a significant downward trend, whereas the proportions of hepatitis C and hepatitis E among those with viral hepatitis have increased annually. The combined scaling exponent and development trends of the five types of hepatitis show significant heterogeneity. Overall, hepatitis C exhibits superlinear characteristics, whereas other types of hepatitis exhibit sublinear characteristics. Different types of hepatitis exhibit distinct epidemic characteristics and require targeted prevention and control measures.